A critical analysis of earthquakes and urban planning in Turkey - Sengezer, B; Koç, E (BLACKWELL PUBL LTD, 2005)
The land use plans and policies of developed countries that live with the threat of earthquakes are gaining importance in reducing or eliminating the long-term threat to people and property. In developing countries, however, these plans and policies seem to increase the level of vulnerability. This paper examines the effects of the earthquakes that have occurred in Turkey since 1992, with a particular focus on urbanisation and planning policies. It is based on extensive surveys carried out on location immediately after the earthquakes in Erzincan and Kocaeli-Golcuk in 1992 and 1999, respectively. The analysis takes into account several factors, including the height of buildings, geological conditions and the construction period. The authors conclude that land use planning can serve as a very useful instrument for mitigating the extent of disaster damage if it is part of an appropriate planning system. In the case of Turkey, the planning system needs to be reorganised for this purpose.The land use plans and policies of developed countries that live with the threat of earthquakes are gaining importance in reducing or eliminating the long-term threat to people and property. In developing countries, however, these plans and policies seem to increase the level of vulnerability. This paper examines the effects of the earthquakes that have occurred in Turkey since 1992, with a particular focus on urbanisation and planning policies. It is based on extensive surveys carried out on location immediately after the earthquakes in Erzincan and Kocaeli-Golcuk in 1992 and 1999, respectively. The analysis takes into account several factors, including the height of buildings, geological conditions and the construction period. The authors conclude that land use planning can serve as a very useful instrument for mitigating the extent of disaster damage if it is part of an appropriate planning system. In the case of Turkey, the planning system needs to be reorganised for this purpose.
Keywords: earthquake; hazard mitigation; land use planning; vulnerability; Environmental Sciences & Ecology; Social Sciences - Other Topics